A scientometric analysis of mobile recommender systems. (19th June 2020) - Madadipouya, Kasra; Shuib, Liyana; Hamid, Suraya
With further advancements in technology, a new emerging topic called 'mobile recommender systems' has gained tremendous momentum. The amount of research on mobile recommender systems can reflect the development of a variety of research topics such as mobile computing and context-aware systems. Hence, performing a scientometric mapping on this topic is needed. However, there is a lack of research in this area that aims to perform a detailed scientometric mapping. The objective of this study is to perform a scientometric mapping related to mobile recommender systems. We analysed publications between 2002 and 2017 indexed in Web of Science. The analysis maps the parameters of total output, the growth of output, authorship, major contributors, thematic trends and emerging topics in the field. Our study serves as a resource for future research by shedding light on how trends in mobile recommender systems research have evolved as well as providing insights into the current state of this field.